Brand Choice Factors on Purchase Decision of Electric Vehicle: In Reference of Nepalese Customers - Manandhar, Raju Bhai (Nepal Journal of Multidisciplinary Research, 2021)
There are various factors which effect on the purchase decision of consumers. Brand choice factor is one of the important to determine the purchase decision. The demand of electric vehicle is increasing because of its contribution in health and environment. Nepalese consumers are also more being attracted towards the use of electric vehicle so in this context, the study conducted with the objective to identify the brand choice factor on purchase decision of electric vehicle. The study was conducted among the 55-electric vehicle of Kathmandu valley. The structured survey questionnaire was administered for the data collection. It was based on quantitative design. Simple random sampling design was adopted to select the respondents. There was no significant difference between male and female, as well as caste groups, whereas there was significant difference between the educational levels on their brand choice factors at the .05 significant levels. The future researcher can study on the role of other factors to determine the purchase decision of electric vehicle consumers.